Benefits of Online Learning for Students of the PPKn Study Program Class of 2020 during the Covid 19 Pandemic - Mawene, Enka; Sialana, F; Soumokil, Agustinus (CV. Rayyan Dwi Bharata, 2023)
Students of the PPKn study program, teacher training faculties and education who during the pandemic used online learning on the one hand have benefits for students but on the other hand there are weaknesses of online learning. Online learning is learning carried out in the network, meaning learning that takes place online using applications that can display a class face-to-face online. Online learning has taken place in the Pancasila and citizenship education study programs since 2020 with the aim of meeting educational standards through the use of information technology.Basically, online learning is a tool or intermediary for the delivery of learning materials, it needs to be used, especially during a pandemic, therefore the use of online applications is one of the most important learning media carried out in learning activities between lecturers and students, teaching and learning activities are a process of forming self-understanding of science, knowledge, Psychic and social, in the implementation of online learning learning applications have an important role in increasing student motivation and interest, Based on the results of the study, researchers found that online learning is independent learning and high interactivity, able to increase memory levels, provide more learning experiences, with text, audio, video and animation all used to convey information, and also provide ease of conveying, updating content, downloading, students can also send emails to other students, send comments on discussion forums, use chat rooms, to videoconference links to communicate directly.